Sobre o acordo com a diocese de Macau e a ilha de Hainan para Cantão, e o distrito de Chão-Hing para Macau (1900)
This 1900 diplomatic memorandum, originating from the Portuguese Embassy to the Holy See in Rome, documents negotiations between the governments of Portugal and France concerning the ecclesiastical jurisdiction of Hainan Island in southern China. The text records that Hainan had been provisionally placed under the Diocese of Macau by the Holy See in 1875–76, but due to limited clergy and logistical challenges, the Bishop of Macau had not effectively evangelised the island. In light of the Paris Foreign Missions Society’s growing capacity within the Apostolic Prefecture of Guangdong, the French government proposed transferring Hainan back to Cantonese ecclesiastical authority. Portugal conditionally assented, requiring in exchange the extension of the Bishop of Macau’s jurisdiction over the district of Chao Hing (Gao Hing), adjacent to existing territories under his spiritual control. The agreement was to be implemented *provisoria tantum ratione*—on a provisional basis only—with territorial delimitations subject to prior approval by the Holy See. The document includes multiple memoranda from 1898–1900 exchanged between diplomatic representatives in Lisbon, Paris, and Rome, including communications involving Mr Avoye, Mr Delcassé, and the Apostolic Nuncio. It reflects the intersection of colonial diplomacy, ecclesiastical administration, and imperial interests in late 19th-century China, illustrating how religious jurisdiction served as both a spiritual and political instrument in Sino-European relations.
Keywords: Apostolic Prefecture of Guangdong; Bishop of Macau; Chao-King district; Colonial Administration Context; Diocese of Macau; Diplomatic Exchanges; Evangelisation Challenges; Franco-Portuguese Diplomatic Negotiations; Hainan Island Ecclesiastical Jurisdiction; Historical Document Analysis; Holy See Jurisdictional Decree; Imperial Interests in Southern China; Late 19th Century Mission Strategy; Limited Clergy Resources; Logistical Constraints; Mr Avoye Correspondence; Paris Foreign Missions Society; Portuguese Embassy to Holy See; Provisional Placement; Sino-European Ecclesiastical Relations; Tantum Ratione Doctrine; Territorial Delimitations; Transcription; Vatican Diplomatic Communications